On the origin of nonequivalent states: how we can talk about preprints - Neylon, Cameron; Pattinson, D.; Bilder, G.; Lin, J. (2016)
Increasingly, preprints are at the center of conversations across the research ecosystem. But disagreements remain about the role they play. Do they "count" for research assessment? Is it ok to post preprints in more than one place? In this paper, we argue that these discussions often conflate two separate issues, the history of the manuscript and the status granted it by different communities. In this paper, we propose a new model that distinguishes the characteristics of the object, its "state", from the subjective "standing" granted to it by different communities. This provides a way to discuss the difference in practices between communities, which will deliver more productive conversations and facilitate negotiation on how to collectively improve the process of scholarly communications not only for preprints but other forms of scholarly contributions.